2013
DOI: 10.17138/tgft(1)215-219
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the causes of bush encroachment in Africa: The key to effective management of savanna grasslands

Abstract: The increase in biomass and abundance of woody plant species, often thorny or unpalatable, coupled with the suppression of herbaceous plant cover, is a widely recognized form of rangeland degradation. Bush encroachment therefore has the potential to compromise rural livelihoods in Africa, as many depend on the natural resource base. The causes of bush encroachment are not without debate, but fire, herbivory, nutrient availability and rainfall patterns have been shown to be the key determinants of savanna veget… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
0
22
0
1
Order By: Relevance
“…The substantial losses of G. senegalensis in 2015 and the observed regrowth are part of natural cycles in a non-equilibrium ecosystem [13,38] and we have affirmed these rainfall controlled dynamics. On the other hand, shrub encroachment and the loss of herbaceous vegetation in southern Africa is considered an undesired effect for livestock farmers [33,39], the situation in Sahel with less rainfall and infertile soils is however different, and the valuation of the effects of gains and losses in woody cover need to be carefully assessed. Moreover, the spreading of single species leads to a poor biodiversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The substantial losses of G. senegalensis in 2015 and the observed regrowth are part of natural cycles in a non-equilibrium ecosystem [13,38] and we have affirmed these rainfall controlled dynamics. On the other hand, shrub encroachment and the loss of herbaceous vegetation in southern Africa is considered an undesired effect for livestock farmers [33,39], the situation in Sahel with less rainfall and infertile soils is however different, and the valuation of the effects of gains and losses in woody cover need to be carefully assessed. Moreover, the spreading of single species leads to a poor biodiversity.…”
Section: Discussionmentioning
confidence: 99%
“…2017, 9, 39 3 of 21 product of the complex interactions between climate, biology, geomorphology, soils, fauna, fire, and human activity over time (see Figures A1-A6 and Table 1). Soils play an important role in defining the contrasting character of the western and eastern parts of the study region.…”
Section: Introductionmentioning
confidence: 99%
“…It has previously been observed that when bush encroachment occurs, high-quality grass species often disappear, leaving behind hardy and less palatable grasses. Further, bush encroachment could occur due to the removal of keystone species and/or the removal of grasses that often help with maintaining the balance of tree-grass interactions [72,73].…”
Section: Tsetse Prevalence and Distribution Patternsmentioning
confidence: 99%
“…The increase in woody species in former grass dominated landscapes is often perceived as negative as it reduces the ability of savanna ecosystems to provide goods and services (De Wit et al 2001;Lesoli et al 2013). For instance woody encroachment results in loss of biodiversity, reduction in capacity of rangelands to support livestock and wildlife, reduced surface stream flows, increase in fire hazards as well as soil erosion (Moleele 2002;Wigley et al 2009;Kgosikoma and Mogotsi 2013;Lesoli et al 2013;O'Connor et al 2014;Kgosikoma et al 2012). In view of the potential negative effects of woody encroachment on savanna ecosystem and projected increase in the bioclimatically suitable area, monitoring and management efforts could target these woody encroachment ''hotspots''.…”
Section: Bioclimatic Variables Of Importancementioning
confidence: 99%